The impact of different antiepileptic drugs on the sedation of children during magnetic resonance imaging - Davarci,Isil (2014)
Background and objectives:The induction and inhibition of cytochrome P450 isoenzymes by antiepileptic drugs lead to changes in the clearance of anesthetic drugs eliminated via hepatic metabolism. We investigated the duration of the sedation and additional anesthetic needs during magnetic resonance imaging in epileptic children receiving antiepileptic drugs that cause either enzyme induction or inhibition.Methods:In American Society of Anesthesiology I–II, 120 children aged 3–10 years were included. Group 1: children using antiepileptic drugs that cause cytochrome P450 enzyme induction; Group 2: those using antiepileptic drugs that cause inhibition; and Group 3: those that did not use antiepileptic drugs. Sedation was induced with the use of 0.05 mg kg−1 midazolam and 1 mg kg−1 propofol. An additional 0.05 mg kg−1 of midazolam and rescue propofol (0.5 mg kg−1) were administered and repeated to maintain sedation. The duration of sedation and the additional sedation needed were compared.Results:The duration of the initial dose was significantly shorter in Group I compared with groups II and III (p = 0.001, p = 0.003, respectively). It was significantly longer in Group II compared with groups I and III (p = 0.001, p = 0.029, respectively). The additional midazolam needed for adequate sedation was increased in Group I when compared with groups II and III (p = 0.010, p = 0.001, respectively). In addition, the rescue propofol dose was significantly higher only in Group I when compared with Group III (p = 0.002).Conclusion:In epileptic children, the response variability to the initial sedative agents during the magnetic resonance imaging procedure resulting from the inhibition or induction of the cytochrome P450 isoenzymes by the antiepileptic drugs mandated the titration of anesthetic agents.